Exploring Muscle Health Deterioration and Its Determinants Among Community-Dwelling Older Adults - Chao, Yuan-Ping; Fang, Wen-Hui; Chen, Wei-Liang; Peng, Tao-Chun; Yang, Wei-Shiung; Kao, Tung-Wei (Frontiers in Nutrition, 2022)
Background Age-related muscle mass and function decline are critical issues that have gained attention in clinical practice and research. Nevertheless, little is known regarding the time course of muscle health progression, and its determinants during this transition should be estimated. Methods We enrolled community-dwelling adults aged ≥65 years during their regular health checkup. The participants’ body composition and muscle function were measured annually from 2015 to 2021. Presarcopenia was characterized by the loss of muscle mass only; dynapenia was defined as low muscle function without changes in muscle mass; and sarcopenia was indicated as a decline in both muscle mass and muscle function. We observed the natural course of muscle health progression during aging. The relationship between muscle health decline and different determinants among old adults was examined. Results Among 568 participants, there was 18.49%, 3.52%, and 1.06% of healthy individuals transited to dynapenia, presarcopenia and sarcopenia, respectively. Significant positive correlations between age, fat-to-muscle ratio (FMR) and the dynapenia transition were existed (hazard ratio [HR] =1.08 and HR =1.73, all p<0.05). Serum albumin level had negative correlation with the dynapenia transition risk (HR=0.30, p=0.004). Participants with these 3 risk factors had the highest HR of dynapenia transition compared to those without (HR=8.67, p=0.001). A dose-response effect existed between risk factors numbers and the risk of dynapenia transition (p for trend <0.001). This positive association and dose-response relationship remains after multiple covariates adjustment (HR=7.74, p=0.002, p for trend <0.001). Participants with two or more than two risk factors had a higher risk of dynapenia transition than those with low risk factors (p =0.0027), and the HR was 1.96 after multiple covariate adjustment ( p=0.029). Conclusion Healthy community-dwelling old adults tended to transit to dynapenia during muscle health deterioration. Individuals with older age, higher FMR, lower albumin level had a higher risk of dynapenia transition; and a positive dose-response effect existed among this population as well.